PROBLEMATICS OF SETTLEMENT OF INHERITANCE RIGHTS OF DAUGHTER WITH SIBLINGS IN THE MAHKAMAH SYAR’IYAH BANDA ACEH AND ACEH - Amri, Aulil (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2023)
This research discusses the Polarization of Judges' Decisions in the Settlement of Sibling Inheritance Rights (Case Study of Decision Number: 193/Pdt.G/2020/MS.Bna AND 21/Pdt.G/2021/MS.Aceh). The formulation of the problem studied is: 1. Why is there a disparity in the judge's decision regarding the position of relatives as heirs in an inheritance dispute at the Religious Court in decision number: 193/Pdt.G/2020/MS.Bna vs. 21/Pdt.G/2021/ MS. Aceh? 2. Has the judge's decision in resolving the dispute over the determination of heirs protected the rights of heirs in accordance with faraidh? This research is normative and practical juridical research, namely library research supported by results in the field in the form of interviews with related functional officials of the Banda Aceh Syar'iyah Court and Aceh Syar'iyah Court. This study concludes that: 1. The disparity in the decisions of the Banda Aceh Syar'iyah Court and the Aceh Syar'iyah Court occurred due to an understanding of the Jumhur Ulama's opinion which stated that a daughter cannot be hindered by a daughter in receiving an inheritance. Jumhur Ulama's definition of "kalalah" is the death of someone who does not have a father or son. This is in line with jurisprudence and the opinion of Ibn 'Abbas, which stipulates that girls can wear the hijab to inherit, but girls cannot wear the hijab inherited from their brothers. 2. The judge's decision at the Banda Aceh Syar'iyah Court in resolving the dispute over the determination of heirs has protected the rights of heirs in accordance with faraidh. This is because the opinion of the jumhur of scholars and the opinion of Ibn 'Abbas are in line with the opinion of the panel of judges. Then the daughter in this case is an adult and has a steady job and income, which is different from the case in jurisprudence.